If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + -2(3 + -1x) = -2(x + 3) -4 + (3 * -2 + -1x * -2) = -2(x + 3) -4 + (-6 + 2x) = -2(x + 3) Combine like terms: -4 + -6 = -10 -10 + 2x = -2(x + 3) Reorder the terms: -10 + 2x = -2(3 + x) -10 + 2x = (3 * -2 + x * -2) -10 + 2x = (-6 + -2x) Solving -10 + 2x = -6 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -10 + 2x + 2x = -6 + -2x + 2x Combine like terms: 2x + 2x = 4x -10 + 4x = -6 + -2x + 2x Combine like terms: -2x + 2x = 0 -10 + 4x = -6 + 0 -10 + 4x = -6 Add '10' to each side of the equation. -10 + 10 + 4x = -6 + 10 Combine like terms: -10 + 10 = 0 0 + 4x = -6 + 10 4x = -6 + 10 Combine like terms: -6 + 10 = 4 4x = 4 Divide each side by '4'. x = 1 Simplifying x = 1
| -16=6+4+3x | | -6x^3+9x^2-3=0 | | 3=y-n+h | | -8=13-7x | | xy=1+3x | | N=y-n+h | | 6x^3-9x^2+3=0 | | yx=1+3x | | x+4.7=-6.2 | | yx=1+3y | | 8x-4=-2x | | 4x^2+4x+21=0 | | (2x-2)+(x+11)=180 | | -7(x+9)=9(k-5)-14k | | -4.9x^2+21x-55=0 | | 4(13-3x)-17=-5x | | c(x)=0.14x | | 49v^3-4v=0 | | 12y+6=6(2y+10) | | 1.2x-0.5=0.1 | | 8x^2-30x-25=0 | | -4.9x^2+21x=55 | | 80=x+(x-10) | | 12-(n-6)+4n-2=n+14 | | x+6.5=-7.6 | | 4+xi=y-7i | | -3(7x+7)-5(x-7)=14 | | X+25+3x=-9+-3x+-15 | | 6g^3-2g^2+4g=0 | | 6x^2-5x-7=-8 | | 7x-127=0 | | 4(4)-2y-7= |